2018
DOI: 10.1017/s0022149x18000676
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of rhinebothriidean tapeworm from the skate Dipturus batis in the Mediterranean Sea

Abstract: Examination of rajid skates off the Algerian coast in the Mediterranean Sea revealed that three of the 33 Dipturus batis Linnaeus, 1758 examined harboured a new tapeworm species: Echeneibothrium algeriensis n. sp. This new species, collected from the anterior half of the spiral valves, is described on the basis of morphological data from light and scanning electron microscopy. The new species differs from previously described Echeneibothrium species by details of the scolex and loculi, total length, the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…comm., 2020), although there have been numerous accounts relating to D. oxyrinchus and D. nidarosiensis ( e.g ., Serena et al ., 2020). Whilst a recent parasitology‐based study has nominally reported ‘ D. batis ’ in the Mediterranean (Benmeslem et al ., 2019), the identification material used by the author pre‐dated the split in the complex, and no specific morphological information was provided, therefore this record should be considered as questionable without further means of confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…comm., 2020), although there have been numerous accounts relating to D. oxyrinchus and D. nidarosiensis ( e.g ., Serena et al ., 2020). Whilst a recent parasitology‐based study has nominally reported ‘ D. batis ’ in the Mediterranean (Benmeslem et al ., 2019), the identification material used by the author pre‐dated the split in the complex, and no specific morphological information was provided, therefore this record should be considered as questionable without further means of confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent descriptions or redescriptions of cestode species commonly include the microthrix pattern observed with SEM, which is usually of taxonomic importance. Unfortunately, the microthrix pattern of the myzorhynchus of rhinebothriideans has only been studied, to our knowledge, in eight (i.e., Echeneibothrium algeriensis , E. cristinae , E. megalosoma , E. multiloculatum , E. williamsi , N. navonae , N. shetlandicum , and Pseudanthobothrium hanseni ) of the 36 species of the family Echeneibothriidae (Benmeslem et al, 2018; Bueno & Caira, 2017; Franzese et al, 2022; Ivanov & Campbell, 2002; Randhawa et al, 2008). Several of those species show a common pattern, with spinitriches restricted to the proximal portion of the myzorhynchus (i.e., AMSP) and filitriches distributed along its entire length (i.e., AMSP and AO).…”
Section: Discussionmentioning
confidence: 99%
“…megalosoma, E. multiloculatum, E. williamsi, N. navonae, N. shetlandicum, and Pseudanthobothrium hanseni) of the 36 species of the family Echeneibothriidae (Benmeslem et al, 2018;Bueno & Caira, 2017;Franzese et al, 2022;Ivanov & Campbell, 2002;Randhawa et al, 2008).…”
Section: Microtriches On Myzorhynchus Surfacementioning
confidence: 99%